Some Exact Solutions of Non-Newtonian Fluid in Porous Medium with Hall Effect Having Prescribed Vorticity Distribution Function (Global Journal of Science Frontier Research, 2014)
Two dimensional motion of an incompressible second grade fluid in a porous medium with Hall effects has been considered. Exact solutions are obtained via inverse method when vorticity distribution is proportional to stream function ψ, perturbed by a quadratic term.
Keywords: non-newtonian fluid; porous medium; hall effect; mhd; steady flow